2000
DOI: 10.1039/b004010j
|View full text |Cite
|
Sign up to set email alerts
|

Energy disposal during desorption of D2 from the surface and subsurface region of Ni(111)

Abstract: The recombination of surface and subsurface D atoms on Ni(111) has been studied using resonance-enhanced multiphoton ionisation (REMPI) to measure the internal state and translational energy distributions of the desorbing product. By detecting formed D 2 during temperature-programmed desorption we were able to examine the reaction between subsurface and surface D atoms, and the recombination of two D atoms chemisorbed on the surface. Translational energy distributions for formed by D 2 recombination of surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Indeed, on the noncatalytic Ti substrate, the onset temperatures for hydrogen desorption significantly differed (by 50 • C) as particle size increased and the surface area decreased accordingly (Figure 5b), in agreement with previous reports [15]. The initial desorption of hydrogen at 210 • C is also consistent with reported thermal desorption spectra of molecular hydrogen adsorbed at Ni surfaces [31][32][33]. It can thus be concluded that the shift in desorption temperature observed on the Ni catalytic substrate from 290 to 390 • C as particle size increased from 68 ± 11 to 421 ± 70 nm is related to rate-limiting steps other than hydrogen recombination at the magnesium surface.…”
Section: Hydrogen Sorption Propertiessupporting
confidence: 81%
“…Indeed, on the noncatalytic Ti substrate, the onset temperatures for hydrogen desorption significantly differed (by 50 • C) as particle size increased and the surface area decreased accordingly (Figure 5b), in agreement with previous reports [15]. The initial desorption of hydrogen at 210 • C is also consistent with reported thermal desorption spectra of molecular hydrogen adsorbed at Ni surfaces [31][32][33]. It can thus be concluded that the shift in desorption temperature observed on the Ni catalytic substrate from 290 to 390 • C as particle size increased from 68 ± 11 to 421 ± 70 nm is related to rate-limiting steps other than hydrogen recombination at the magnesium surface.…”
Section: Hydrogen Sorption Propertiessupporting
confidence: 81%
“…In both reports it was pointed out that the activation energy barrier for the process starting from surface H and CH 3 is considerably lower in energy, and the increased reactivity when the Ni catalyst is prepared with subsurface H atoms is not due to a new reaction pathway but rather the additional energy given to the initial state of the desorption process by driving the H atoms into subsurface sites. 7,8 The reactivity of subsurface deuterium on Ni͑111͒ has been studied by Wright et al 9,10 Temperature-programmed desorption experiments of D in both subsurface and surface sites show enhanced D 2 associative desorption on Ni͑111͒ at 180 K, as compared to a thermal base line. The angular distribution of desorbing molecules is consistent with subsurface D atoms surfacing at vacant sites and diffusing on the surface before combining to form D 2 .…”
Section: Introductionmentioning
confidence: 98%
“…Lin et al 25 reported the direct imaging of subsurface hydrogen atoms in Pd nanoparticles. Wright et al 26 examined the reaction between subsurface and surface D atoms on Ni(111). The detected product translational excitation suggested that the recombination was direct at low temperatures, whereas the indirect channel started to work at high temperatures due to the decrease in the energy release.…”
Section: Introductionmentioning
confidence: 99%